2012
DOI: 10.3349/ymj.2012.53.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Kidney Stones by Extracorporeal Shock Wave Lithotripsy Is Associated with Delayed Progression of Chronic Kidney Disease

Abstract: PurposeThis study aimed to elucidate whether stone removal by extracorporeal shock wave lithotripsy (ESWL) is associated with delayed chronic kidney disease (CKD) progression.Materials and MethodsWe conducted a retrospective analysis of 131 nephrolithiasis patients with stage 3 and 4 CKD. We collected baseline clinical and laboratory data, kidney stone characteristics, and history of receiving ESWL. We classified study patients into two groups according to whether they underwent ESWL or not (Non-ESWL group vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…17 A 19-year follow-up retrospective study of 288 patients found that the rate of renal insufficiency (*5%) was unchanged after SWL despite higher rates of obesity and diabetes. 23 In contrast, a 15-month follow-up prospective study on 134 patients reported that SWL was associated with a higher prevalence of CKD after treatment, and that BMI was a risk factor for CKD after SWL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A 19-year follow-up retrospective study of 288 patients found that the rate of renal insufficiency (*5%) was unchanged after SWL despite higher rates of obesity and diabetes. 23 In contrast, a 15-month follow-up prospective study on 134 patients reported that SWL was associated with a higher prevalence of CKD after treatment, and that BMI was a risk factor for CKD after SWL.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The few reports addressing the long-term outcome of SWL in stone patients with chronic renal insufficiency would also suggest that SWL is safe in such a vulnerable cohort. [15][16][17] The etiology of CKD in these patients is thought to be obstructive uropathy with SWL treatment providing relief from obstruction and generally improving renal function. However, there is limited information on whether SWL treatment may exacerbate the risk for renal functional impairment in patients with MetS-obesity, hypertension, insulin resistance, and other features of MetS being risk factors for CKD.…”
mentioning
confidence: 99%
“…Not only do urologic procedures manage the kidney stone event itself, our study provides evidence that they may help to prevent long-term deterioration in kidney function as seen in previous studies. 6,[12][13][14][15][16][17] Limitations There were several limitations to this study. Patients with kidney stones were identified either by seeking medical care for symptoms related to an acute episode or incidentally on imaging such as computed tomography or ultrasound.…”
Section: Hazards Among Stone Formers After Urologic Proceduresmentioning
confidence: 98%
“…14 On the contrary, Yoo et al 15 found, in a retrospective analysis of 131 nephrolithiasis patients with stage 3 and 4 CKD and mean observation period of 3.2 years, that stone removal by ESWL was associated with delayed deterioration of renal function in CKD patients with nephrolithiasis. Percutaneous renal surgery in the solitary kidney is safe, and it results in renal function preservation.…”
mentioning
confidence: 99%
See 1 more Smart Citation